2020
DOI: 10.1017/s1751731119001265
|View full text |Cite
|
Sign up to set email alerts
|

Performance, carcass characteristics and meat quality of Nellore cattle supplemented with supranutritional doses of sodium selenite or selenium-enriched yeast

Abstract: The enrichment of meat with selenium is important to improve the intake of selenium by humans. The effects of supranutritional doses of sodium selenite or selenium-enriched yeast on performance, carcass characteristics and meat quality were evaluated using 63 Nellore cattle in a completely randomized design with two sources (sodium selenite and selenium-enriched yeast), three levels (0.3, 0.9 and 2.7 mg Se/kg DM) and control treatment (without addition of selenium). Final body weight (BW), average daily gain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Improved beef meat quality parameters (e.g., color stability) and increased Se concentration in the muscles of Charolais bulls supplemented with organic Se (0.2 mg/kg DM) for 60 days were observed by Grossi et al [57]. The selenium concentration in the meat of Nellore cattle was higher in animals supplemented with organic Se (0.3, 0.9, and 2.7 mg/kg DM) compared to organic Se [68]. Results obtained by Hall et al [69] and Galbraith et al [70] also showed better bioavailability of the organic forms of Se compared to the inorganic form.…”
Section: Selenium Absorption and Bioavailabilitymentioning
confidence: 83%
“…Improved beef meat quality parameters (e.g., color stability) and increased Se concentration in the muscles of Charolais bulls supplemented with organic Se (0.2 mg/kg DM) for 60 days were observed by Grossi et al [57]. The selenium concentration in the meat of Nellore cattle was higher in animals supplemented with organic Se (0.3, 0.9, and 2.7 mg/kg DM) compared to organic Se [68]. Results obtained by Hall et al [69] and Galbraith et al [70] also showed better bioavailability of the organic forms of Se compared to the inorganic form.…”
Section: Selenium Absorption and Bioavailabilitymentioning
confidence: 83%
“…Previous findings were consistent with our results. Animals consuming a diet with increasing Se levels exhibited an increase in HCW (Silva et al, 2020). The addition of Se improved the commercial and biological carcass yield (Hernandez-Calva et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Se supplementation improved HCW due to a higher proportion of muscle tissue in individual ribs and fore shank (Table 2). Dressing and HCW were shown to be affected by different variables, including visceral organ mass (Silva et al, 2020). On the other hand, Mahmood et al (2018) reported that the increases were due to a higher proportion of muscle tissue in HCW in the rack, loin, and leg regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These native cattle breeds have many specific genes and potentials for meat production (26,27). The meat quality Meat color mainly reflects changes in biochemical, physiological, and microbiological properties in muscle (28). The observation of meat color is widely used as an effective way to evaluate meat quality by consumers.…”
Section: Discussionmentioning
confidence: 99%